First term at Malory towers - Blyton, Enid. (b)
There are plenty of adventures to be had in Darrell's first term at boarding school. Life at Malory Towers is full of excitement - but can Darrell learn to keep her terrible temper under control?
Keywords: Malory Towers (Imaginary place) -- Juvenile fiction; Boarding schools -- Juvenile fiction; Girls -- Fiction